Features of implementation of the principle of respect for the rights and freedoms of man and citizen (Journal of actual problems of jurisprudence, 2018)
The article deals with the problem of the protection of the natural and integral human rights as enshrined in the Universal Declaration of Human Rights and other international legal instruments, which effectiveness of the organizational and legal solutions are different widely spread in many countries. Also shown are the facts of the contradictions between state and society, state institutions and civil associations because of the abuse of power and corruption in government and the infringement of political, economic and civil rights.Emphasis is placed on the fact that due to the huge social and international significance of the problem of human rights has a century of history, philosophy, and scientific basis. In recent years in connection with the deployment of experts from many countries globalization investigate and recommend different effective system for the natural and integral rights of human and citizen in connection with the provisions of relevant international instruments.Key words: human rights, the theory of social contract, alienate, Ombudsman, Human Rights Commissioner.